Survey on Mobile Healthcare - Arun, NG; Surya, SG; Azath, M (International Journal of Computer Sciences and Engineering, 2015)
There are several factors behind the progress of the mHealth field. The first factor concerns the constraints felt by healthcare systems of developing nations. These constraints includes high growth in population, a high burden of disease prevalence, large numbers of rural inhabitants, low health care cost, and limited financial resources to support healthcare infrastructure and health information services. The second factor is the recent rapid rise in mobile phone usage in developing countries to large portion of the healthcare industry, as well as the population of a country as a whole. With increasing access of mobile phones to all segments of a country, including rural areas, the importance of reducing information and transaction costs in order to deliver healthcare improves. Wireless body area networks (WBANs) are emerging as important networks, applicable in various fields. In recent years, clinicians are beginning to utilize Mobile Health Systems (mobile devices with clinical applications) when delivering healthcare services to patients at the point-of-care. There are several applications like Healthcare Smart Hospitality, Monitoring System, and Continuous patient monitoring system are under Body Area Network (BAN) technology. mHealth technology helps physicians to remotely monitor patients’ health and enables each person to manage their own health more easily. The key factors which help mobile healthcare system infusion are time-criticality, availability of the technology, habit of people, technology, etc. Here we have to consider power efficient protocols, monitoring and sensing, system architectures, security and sensing. Body sensor networks provide a unique platform for the development of pervasive healthcare, physically engaged gaming and well being.